Results of the research cruises of FRV' Walther Herwig' to South America. LXXIV. Benthobatis kreffti n. sp (Chondrichthyes, Torpediniformes, Narcinidae), a new deep-water electric ray from off South Brazil and the third species of the genus. - Rincon, G.; Stehmann, MFW; Vooren, C. M. (Urban & Fischer Verlag, 2001)
Benthobatis kreffti n. sp. is described as the third species of this genus of blind deep-water electric rays, based on 150 specimens taken from the continental slope off South Brazil. The new species is the smallest within the genus (TL less than 300 mm) and is compared with both congeners, B. marcida from the north-western Atlantic and B. moresbyi from the northern Indian Ocean. B. kreffti is characterised beyond its small size mainly by plain dark colouration dorsally and a white underside, with dark margins of disc and pelvics, as well as by totally degenerated eyes almost no longer visible externally. The new species is diagnosed further by very low tooth counts of 9 to 13 rows and lack of folds, keels or ridges on sides of tail.